Gestión crediticia del área agrícola y su incidencia socioeconómica en los clientes del banco nacional de Fomento sucursal Quevedo, periodo 2013-2014, Plan de capacitación interinstitucional. - Ramírez Pettao, Odalis (2015)
This thesis evaluates the credit management of the agricultural area and its socio-economic impact on customers of the National Bank Branch Development Quevedo, a fin to establish strategies that will enable mitigation of weaknesses and threats in the institution, and also detected the impact Relationship Do society and economic developments. Theoretical Development Support in scientific knowledge, analysis of the types of credit and the different activities that are financed, legal, statutes, regulations ,: regulations, and credit policy conformity with the plans and programs implemented paragraph Finance Socioeconomic Development and Growth in families. The research methodology was based on the documentary and field part; Were the methods used: induction, statistical, descriptive, forecast, analytical, statistical, and techniques for obtaining information from the surveys was established as an instrument of research. The following hypothesis is proved: The Agricultural Credit Management Development Bank area of Quevedo, positive impact on the socioeconomic development of the clients of the National Bank of Development of the City of Quevedo. The proposed alternative paragraph This research project was the design of one interagency plan Training Purpose scam contribute to sustainable socioeconomic and sustainable customer of National Development Bank Development, whose work will be done in conjunction with Officials from the Ministry of Agriculture, Livestock and Fisheries (MAGAP). The Inter Alliance to consider it possible to expand the knowledge col Vision Training provide bank customers, as well as promote the welfare system in the Economic and social Development Generating productive micro and small enterprises applying maximizing.